Employer Wellness Programs Challenged in Court - Rothstein, Mark A. (The Hastings Center report, 2017)
Many employers faced with rising health care costs have adopted “voluntary” wellness programs that urge employees to engage in various health-promotion activities, such as smoking cessation and weight reduction. In the proper setting, measures to promote a more healthful lifestyle are difficult to question, but there is little compelling evidence that workplace wellness programs have significant, sustained health benefits or substantially reduce health care costs other than through cost-shifting to unhealthy employees. Congressional support for workplace wellness programs has persisted on a bipartisan basis for the last twenty years, and the incentives that current statutes allow employers to offer employees have become strong enough that the voluntariness of the programs has been called into question. In recent months, the battleground has shifted to the courts, where federal regulations and employer practices have been challenged. Three recent or pending cases raise questions about whether the incentives are coercing employees into the programs.